(untitled) (Cadernos de Sociomuseologia, 2016)
In this article, we discuss the different phases of the research project Expographic Innovation in Educational Context , from the conception to its operation. The project, was developed at the Lusophone University of Humanities and Technologies (ULHT) and resulted from a partnership between the Interdisciplinary Center for Studies in Education and Development (CeiED) and the Experimental Laboratory of Museology and Education (LEME) . The project aimed to develop expographic methodologies in secondary schools and disseminate resources, particularly in the context of new information technologies and innovation. Keywords: expographic innovation, new technologies, school contexto